Association between polycystic ovary syndrome and the risk of pregnancy complications: A PRISMA-compliant systematic review and meta-analysis. Issue 51 (December 2016) - Yu, Hai-Feng; Chen, Hong-Su; Rao, Da-Pang; Gong, Jian
Abstract: Background: Polycystic ovary syndrome (PCOS) is inconsistently associated with increased risk of adverse pregnancy outcomes. The purpose of this meta-analysis was to summarize the evidence regarding the strength of the association between pregnancy in women with PCOS and pregnancy complications. Methods: We systematically searched PubMed, EmBase, and the Cochrane Library to identify observational studies up to January 2016. The primary focus was pregnancy outcomes, including gestational diabetes mellitus (GDM), preeclampsia, pregnancy-induced hypertension (PIH), preterm delivery, cesarean delivery, oligohydramnios, and polyhydramnios. Effect estimates were pooled using the random-effects model. The analysis was further stratified by factors that could affect these associations. Results: We included 40 observational studies that reported data on a total of 17, 816 pregnancies with PCOS and 123, 756 pregnancies without PCOS. Overall, PCOS in pregnancy was associated with greater risk of GDM, preeclampsia, PIH, preterm delivery, cesarean delivery, miscarriage, hypoglycemia, and perinatal death. However, PCOS in pregnancy had little or no effect on oligohydramnios, polyhydramnios, large-for-gestational age (LGA), small-for-gestational-age (SGA), fetal growth restriction (FGR), preterm premature membrane rupture, fasting blood glucose (FBG), high-density lipoprotein (HDL), low-density lipoprotein (LDL), triglyceride, total cholesterol, congenital malformation, macrosomia, and respiratory distress syndrome. Subgroup analysis suggested that these associations might be influenced by study design and pre-BMI. Conclusion: PCOS in pregnancy is associated with a significantly increased risk of adverse pregnancy, fetal, and neonatal outcomes. Abstract : Supplemental Digital Content is available in the text